Electronic Human Resources Management (e-HRM) Adoption Studies: Past and Future Research - Winarto Winarto (Universitas Pelita Harapan, 2018)
Electronic human resource management (e-HRM) systems become more widely used by profit and non-profit organization. However, the field currently lacks sound theoretical frameworks that can be useful in addressing a key issue concerning the implementation of e-HRM systems, in particular to obtain a better understanding of the factors influencing the adoption of e-HRM systems. The objective of this paper is to provide a foundation towards the development of a theoretical framework for the implementation of e-HRM systems and develop a conceptual model that would reflect the nature of e-HRM systems’ adoption through systematic literature review. Adopting Crossan and Apaydin’s procedure of systematic review, this paper investigated 21 empirical papers of electronics human resources management, then categorized them into 4 characteristics which influence the adoption; System and technology characteristics; Organizational characteristics; User/individual characteristics, and Environmental and contextual characteristics. Finally, the e-HRM adoption research framework is drawn and based on the framework; avenues for future research are discussed. Bahasa Indonesia Abstrak: Manajemen sumber daya manusia elektronik (selanjutnya disebut dengan e-HRM) semakin banyak digunakan oleh organisasi profit dan nonprofit. Namun, bidang dan topik ini belum memiliki kerangka teori yang mapan, yang dapat digunakan untuk menganalisis isu-isu terkait penerapan e-HRM, terutama mengenai faktor-faktor yang mempengaruhi adopsi sistem e-HRM. Tujuan penelitian ini adalah untuk memberikan landasan bagi pengembangan kerangka teoritis untuk implementasi sistem e-HRM dan mengembangkan model konseptual yang akan menggambarkan adopsi sistem e-HRM melalui tinjauan literatur sistematis. Mengadopsi prosedur dan metode Crossan dan Apaydin untuk melakukan telaah literatur secara sistematis, paper ini menyelidiki 21 publikasi empiris manajemen sumber daya manusia elektronik dari 2 database internasional; Business Source Premier dan Social Science Citation Index (SSCI), kemudian mengelompokkannya ke dalam 4 karakteristik yang mempengaruhi adopsi e-HRM; (1). Karakteristik sistem dan teknologi, (2). Karakteristik organisasi, (3). Karakteristik pengguna / individu, dan (4). Karakteristik lingkungan dan kontekstual. Paper ini juga menggambarkan kerangka penelitian adopsi e-HRM serta usulan-usulan untuk penelitian mendatang.